GREEN SUSTAINABLE TECHNOLOGY AND MANAGEMENT - Yakhshieva Zebo Rashidovna; Hojimatov Hojiakbar Alisher ogli (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract: This article examines the current status of green sustainable technologies and management and their economic and environmental benefits. The important role of green sustainable technologies and management in development, reducing energy use and preserving the environment is discussed.